Mediation and knowledge. On some reasons for Adorno's negative dialectic - Escobar Moncada, Jairo (Estudios de Filosofía, 2004)
The goal of this essay is fo present some of the central topics of Adorno's Negafve Dialectics. Especial attention is devoted to the concept of mediation and its relations with the concept of non-identity, and to the concept of subject and object Adorno's atempt to owereome imminently the tight duality subject-object made by modern philosophy, and the underlying concept of conaousness is very imponant, that is wny it is so difficult to consider Adorno, as Habermas does, to be a philosopher trapped in the oporias of the philosophy of conciousness.